Assessing Consensus Between UK Renal Clinicians on Listing for Kidney Transplantation: A Modified Delphi Study. Issue 5 (May 2018) - Tonkin-Crine, Sarah; Pruthi, Rishi; Taylor, Dominic M.; Leydon, Geraldine M.; Calestani, Melania; Oniscu, Gabriel C.; Bradley, J. Andrew; Tomson, Charles R.; Bradley, Clare; Dudley, Christopher; Watson, Christopher J.E.; Draper, Heather; et al.
Abstract : Background: It is well recognized that there is significant variation between centers in access to kidney transplantation. In the absence of high-grade evidence, it is unclear whether variation is due to patient case mix, other center factors, or individual clinician decisions. This study sought consensus between UK clinicians on factors that should influence access to kidney transplantation. Methods: As part of the Access to Transplantation and Transplant Outcome Measures project, consultant nephrologists and transplant surgeons in 71 centers were invited to participate in a Delphi study involving 2 rounds. During rounds 1 and 2, participants rated their agreement to 29 statements covering 8 topics regarding kidney transplantation. A stakeholder meeting was used to discuss statements of interest after the 2 rounds. Results: In total, 122 nephrologists and 16 transplant surgeons from 45 units participated in rounds 1 and 2. After 2 rounds, 12 of 29 statements reached consensus. Fifty people participated in the stakeholder meeting. After the stakeholder meeting, a further 4 statements reached agreement. Of the 8 topics covered, consensus was reached in 6: use of a transplant protocol, patient age, body mass index, patient compliance with treatment, cardiac workup, and use of multidisciplinary meetings. Consensus was not reached on screening for malignancy and use of peripheral Doppler studies. Conclusions: The Delphi process identified factors upon which clinicians agreed and areas where consensus could not be achieved. The findings should inform national guidelines to support decision making in the absence of high quality evidence and to guide areas that warrant future research. Abstract : Supplemental digital content is available in the text.